Sosialisasi Keselamatan dan Keamanan Laboratorium IPA di SMA 1 Pangkalan Baru, Kampar - arief yandra putra; fitri mairizki (Universitas Lancang Kuning, 2020)
The laboratory has an important role in the teaching and learning process. The laboratory with all its materials and equipments is a place that has the potential to cause danger for humans and the environment. Laboratory safety and security management are the responsibility of both the laboratory assistant and laboratory user. Based on the initial survey, the school already has a science laboratory but the tools and materials are poorly organized and poorly administered. The method used in this community service were socialization about the organization and administration of laboratory, socialization about safety and security laboratories related to the management of laboratory equipments and materials, demonstration and evaluation. In general, this community service activity ran successfully as planned. Participants in the activity were very enthusiastic and actively participated during the activity. Based on evaluation results, it was known that students' knowledge about laboratory safety and security has increased after participating in this community service.